The Effect of Virtual Simulation Software on Nursing Students' Academic Performance and Engagement - Guangjun, Xu; Lu, Lee Hsing (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: This study aimed to achieve three core objectives: (a) to assess how Virtual Simulation Software (VSS) affects nursing students’ theoretical knowledge and skill performance relative to traditional methods; (b) to evaluate how perceptions of VSS usefulness and ease of use shape intention to use it; and (c) to investigate how this intention influences learning engagement. Research design, data and methodology: A quasi-experimental pre-test/post-test control group design was adopted with a follow-up survey. Two classes of 40 second-year nursing students from a Chinese vocational college were divided into an experimental group using VSS and a control group with traditional training for ten weeks. Academic performance was measured through knowledge and skills tests, and student engagement and technology acceptance were evaluated via surveys. Data were analyzed using independent t-tests and Simple linear regression. Results: The results showed statistically significant improvements (p < 0.001) in theoretical knowledge and skill performance from pre-test to post-test in both the experimental and control groups. Regression analysis indicated that both perceived usefulness and ease of use of VSS positively influenced students' intention to use it, with perceived usefulness being a stronger predictor. Conclusions: These findings suggest that integrating VSS into nursing curricula can enhance student engagement and performance, validating VSS as a valuable addition to traditional training and providing practical insights for educators to improve nursing education quality.